Soil microbial life history strategies covary with ecosystem multifunctionality across aridity gradients - Tao Zhou; Manuel Delgado-Baquerizo; Chengjie Ren; Nianpeng He; Zhenghu Zhou; Yanghui He (Proceedings of the National Academy of Sciences, 2025)
Aridity thresholds shape ecosystem functions worldwide. Despite the importance of soil microbiomes in engineering ecosystem processes, the specific strategies employed by soil microbiomes to support ecosystem multifunctionality (EMF) across aridity gradients remain virtually unknown. Here, we investigated 474 soil samples across a continental-scale aridity gradient and identified an aridity threshold beyond which plot-level EMF declines sharply. Microbial habitat and decomposition functions were among the last to respond to aridity, with thresholds occurring under more arid conditions compared to plant productivity and soil fertility. Combining metagenomic sequencing with physiological assays to characterize microbial life history strategies of high yield (Y), resource acquisition (A), and stress tolerance (S), we introduce a microbial trait-based framework to mechanistically link community-level microbial life history strategies to EMF. Our results reveal that microbial Y-strategy is positively correlated with EMF across aridity gradients, A-strategy exhibits a negative association with EMF across aridity gradients, and S-strategy is negatively correlated with EMF in arid ecosystems. Collectively, this study offers empirical evidence and insights into how aridification interacts with soil microbiomes in shaping EMF, highlighting the pivotal role of microbial life history strategies in understanding the mechanisms behind EMF variation in an increasingly arid world.